The fetal safety of fluoxetine: a systematic review and meta-analysis - Riggin, Lauren; Frankel, Zipora; Moretti, Myla; Pupco, Anna; Koren, Gideon (Journal of obstetrics and gynaecology Canada, 2013)
Fluoxetine is the selective serotonin reuptake inhibitor (SSRI) with the longest clinical use. Published reports regarding its fetal safety are contradictory. We aimed to establish the fetal safety of the drug. We performed a systematic review of the literature, searching PubMed, Medline, and Embase from inception to August 31, 2012, for cohort and case-control studies in which women were exposed to fluoxetine during the first trimester and compared outcomes with those of unexposed control subjects. Twenty-one studies met the inclusion criteria. The odds ratio for major malformations associated with maternal fluoxetine use in cohort studies was 1.12 (95% CI 0.98 to 1.28). The studies included were homogeneous. Fifteen cohort studies evaluated cardiac malformations and yielded an overall odds ratio of 1.6 (95% CI 1.31 to 1.95). These studies also were homogeneous. In contrast, two case-control studies assessing cardiac malformations yielded a combined odds ratio of 0.63 (95% CI 0.39 to 1.03). The apparent increased risk of fetal cardiac malformations associated with maternal use of fluoxetine has recently been shown also in depressed women who deferred SSRI therapy in pregnancy, and therefore most probably reflects an ascertainment bias. Overall, women who are treated with fluoxetine during the first trimester of pregnancy do not appear to have an increased risk of major fetal malformations.